Prediction successful prostaglandin ( pge2 ) induction of labour in primiparous term pregnancy by measuring cervical length using transvaginal ultrasound - Azhari, Syahrul Azwan (2020)
Purpose of this study is to determine the correlation between the cervical length measured by transvaginal ultrasound with successful vaginal delivery following prostaglandin E2 induction in primiparous term pregnancy This is prospective observational study to determine the correlation between the cervical length measured by transvaginal ultrasound and successful prostaglandin induction of labour in primiparous term pregnancy. Transvaginal ultrasound used to determine cervical length and digital examination of the cervix is performed to determine the bishop score. If bishop score < 5, prostaglandin ( PGE2 ) will be inserted, and will reassessed after 6 hours. If bishop score remain unfavourable, then prostaglandin will be inserted ( maximum 3 times ). Data entry and analysis performed using SPSS version 12. The p value < 0.05 is consider significant Total 90 primiparous term pregnancy women were successfully recruited. 66 ( 77.3% ) of them successfully delivered vaginally, whereas 24 ( 26.7% ) of them were delivered via emergency caesarean section. Out of 24 women delivered via emergency caesarean section, 5 ( 5.6% ) of them were due to acute fetal distress. By using multivariate analysis, only cervical length was statistically significant ( AOR: 34.4, 95% CI = 5.6 – 211.9 ) in predicting successful prostaglandin E2 induction. Using receiver operating characteristic ( ROC ) curve, the cut off value of the cervical length that associated with successful prostaglandin E2 induction in primiparous term pregnancy was 3.1cm with sensitivity 83.6% and specificity 70.6%. Beside that, induction of labor using prostaglandin in primiparous term pregnancy did not cause negative impact to the newborn. Cervical length measured by transvaginal ultrasound prior induction of labour using prostaglandin E2 among primiparous term pregnancy able to predict successful induction process. Induction of labour using prostaglandin E2 did not cause harm to the newborn.